Networked media and information ocean literacy: a transformative approach for UN ocean decade - Gerhardinger LC; Colonese AC; Martini RG; da Silveira I; Zivian A; Herbst DF; Glavovic B; Calvo ST; Christie P (Springer Nature Limited, 2024)
The United Nations’ Ocean Decade calls for co-designing transformative science, ocean networks, and learning strategies to address ocean health decline and deep-blue social divides in ocean governance. Yet the transformative capacity to advance ocean sustainability pathways shared by the UN Ocean Decade ecosystem of partners is still under-realized in the early stages of this global campaign. This paper explores the conceptual and institutional implications of the combined use of marine learning networks (MLNs) and media and information ocean literacy (MIOL) approaches to strengthen capacities for ocean governance systems’ transformation (leadership, strategies, skills, and actions). We build upon an empirical case study of the self-organized, youth-led Brazilian Future Ocean Panel, applying a regional alternative to such a combined approach (namely Social-Environmental Educommunication) during a four-year transdisciplinary program. We reveal the synergistic benefits of MLNs and MIOL in empowering early-career ocean professionals and fostering their transformative capacity in ocean policymaking. Our findings emphasize the practical implications of these approaches for advancing ocean governance systems transformations in other regions. Insights are shared on MLNs and MIOL applications in the pursuit of transdisciplinary solutions, ocean governance transformation, capacity development, and effective responses to foundational challenges facing the UN Ocean Decade’s global efforts toward sustainability.